Application of Allogeneic Human Acellular Dermal Matrix Reduces the Incidence of Fistula in Hypospadias Repair - Wu, Shijian; Ye, Chenglong; Yang, Huai; Chen, Bote; Nie, Haibo; Li, Shaowei (Frontiers in Pediatrics, 2022)
Background: Urethrocutaneous fistula is one of the most common complications arising from hypospadias surgery. The purpose of our study was to investigate the effectiveness and safety of allogeneic human acellular dermal matrix (HADM) application as a means of preventing the occurrence of urethrocutaneous fistula following hypospadias surgery. Methods: This is a non-randomized study of 219 cases (out of 270 patients with hypospadias) which satisfied inclusion and exclusion criteria. These patients were divided into two groups: 101 HADM patients, and 118 control patients (who did not receive HADM). In the control group, 77 boys were treated by single-stage urethroplasty (TIP) and 41 underwent staged urethroplasty (Thiersch-Duplay). In the HADM group, 59 boys underwent the TIP and 42 underwent the Thiersch-Duplay. In the postoperative period, we recorded the incidence of infection, urethrocutaneous fistula, and urethral stricture complications in these two groups of patients. The effectiveness and safety of HADM in preventing urethrocutaneous fistula following hypospadias surgery were evaluated according to these indicators. Results: In the control group, following the operation there were 16 cases of infection, 38 cases of urethrocutaneous fistula after extubating, and 5 cases of urethral stricture. In the HADM group, there were 19 cases of postoperative infection, 12 cases of urethrocutaneous fistula after extubating, and 5 children with urethral stricture. In comparing the two groups, it was found that the postoperative infection rate (13.6% versus 18.8%) and the incidence of urethral stricture (4.2% versus 5.0%) were not statistically significant (P>0.05), while the postoperative urethrocutaneous fistula rate (32.2% versus 11.9%) was statistically significant (P<0.001). Conclusion: It is found that HADM application can significantly reduce the incidence of urethrocutaneous fistula complications, without increasing the risk of infection and urethral stricture.